2021
DOI: 10.1126/sciadv.abc4587
|View full text |Cite
|
Sign up to set email alerts
|

Human population dynamics and Yersinia pestis in ancient northeast Asia

Abstract: We present genome-wide data from 40 individuals dating to c.16,900 to 550 years ago in northeast Asia. We describe hitherto unknown gene flow and admixture events in the region, revealing a complex population history. While populations east of Lake Baikal remained relatively stable from the Mesolithic to the Bronze Age, those from Yakutia and west of Lake Baikal witnessed major population transformations, from the Late Upper Paleolithic to the Neolithic, and during the Bronze Age, respectively. We further loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 102 publications
(129 reference statements)
2
42
0
Order By: Relevance
“…Population genomics from human archaeological finds can help to obtain a better understanding about past migrations and population affinities [ 4 , 5 , 8 ]. By analysing both the human and non-human fraction of ancient DNA, we can explore these past people and the microorganisms that were associated with them [ 15 , 22 , 73 , 88 ]. In this research we have combined a human population genomics analysis with that of the oral bacterium T. forsythia .…”
Section: Discussionmentioning
confidence: 99%
“…Population genomics from human archaeological finds can help to obtain a better understanding about past migrations and population affinities [ 4 , 5 , 8 ]. By analysing both the human and non-human fraction of ancient DNA, we can explore these past people and the microorganisms that were associated with them [ 15 , 22 , 73 , 88 ]. In this research we have combined a human population genomics analysis with that of the oral bacterium T. forsythia .…”
Section: Discussionmentioning
confidence: 99%
“…The Altaic languages, including Mongolic, Tungusic, and Turkic, are widely distributed in northern East Asia, Siberia, and part region of Central Asia. Previous studies from a genetic perspective have mainly demonstrated the northern East Asian affinity of Mongolic and Tungusic-speaking populations based on the genome-wide single-nucleotide polymorphism (SNP) data or sharing IBD fragments (Yunusbayev et al, 2015;Pugach et al, 2016;Jeong et al, 2020;Kilinc et al, 2021). Based on the large-scale sampling of the ancient and present-day populations from Mongolia, Lake Baikal, to Amur River Basin, it is observed that the Mongolians and Tungusic-speaking groups have a higher proportion of genetic component related to the Devil's Gate people who were early Neolithic hunter-gatherers in northeastern East Asia dating to more than 7.7 thousand years ago (Siska et al, 2017), as well as Mongolians Neolithic people (Jeong et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…Younger representatives of this lineage exhibit admixture with the west Eurasian population after its movement into Northeast Asia (e.g., Salkhit [Mongolia] dating to ~34,000 cal BP, AR19K [Amur River Basin] dating to ~19,000 cal BP) (Mao et al, 2021; Massilani et al, 2020; Yu et al, 2020), and the Ancient Native American (ANA) 1 genome reflects as much as 30%–40% contribution from the West Eurasian lineage (e.g., Mao et al, 2021; Yang et al, 2020). The East Asian lineage is present in the Lena Basin (central Siberia) by ~17,000 cal BP and in western arctic Beringia by 10,000 cal BP (Kılınç et al, 2021; Sikora et al, 2019).…”
Section: Discussionmentioning
confidence: 99%